GENETIC DIVERSITY IN RESTORER LINES OF HYBRID RICE (Oryza sativa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
An experiment was conducted with 30 restorer lines to identify most diverse lines in respect of morphological traits for developing heterotic rice hybrids. Thirty restorer lines were classified into four distinct clusters based on mean values of different morphological traits and days to maturity. Again these restorer lines were partitioned into very early, early, medium and late maturing groups. Only one line in very early maturing group had tall plant stature with maximum thousand grain weight but less in yield potential. Early maturing group contained 8 lines from different clusters having short plant stature with short flag leaf and moderate yielding ability. Medium maturing group included 13 lines characterized by medium plant stature with high tillering, excellent spikelet fertility, high grains per panicle and very good yielding ability. Late maturing group contained 8 lines featured by tall plant stature with excellent yield and yield contributing characters. Late maturing restorers BR827R, BR168R and BR736R had maximum genetic distance from centroid indicating extent of heterosis and very high yielding ability. Combining ability and heterosis study with short duration CMS lines may be fruitful for the development of desired hybrid.DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18662